The Use of Simulation as a Pedagogical Device - Porter, John C.; Sasieni, Maurice W.; Marks, Eli S.; Ackoff, Russell L. (Management Science, 1966)
A general simulator of production-inventory systems was developed and used in the classroom to present the student with symptoms and data rather than well-formulated problems. Students were required to analyze and diagnose the situation, formulate the problem, construct appropriate models, organize raw data, and find a solution to the problem. They were permitted to test and evaluate their solutions experimentally. In this way an effort was made to provide students with experience in all phases of operations research, not merely with mathematical exercises in constructing and solving models. The simulator, which was programmed for a computer, presented situations of increasing complexity under direction from the instructor.